PERUBAHAN FATWA - Sopa AR (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Since fatwa is one of dynamical Islamic thought products, the change of it is something natural. It is formulated by doing ijtihad so that it my change because of the changes of argumentations, benefits (maslahah), and customs that become its base. Therefore, the change of the fatwa of Indonesian Ulama Council (MUI) dealing with kiblat should be faced fairly because the change merely occurs on the dictum of the three points above, i.e. changing Westwards into Northwest as the Kiblat of Indonesian Muslims. Such a change happens not because of the new argumentation or the maslahah change, but the different approach. The first fatwa No.03 of 2010 only uses fiqh approach while the second fatwa No. 05 of 2010, as the revision of the first fatwa, uses scientific approach, astronomy, besides using fiqh. The second one, as a matter of fact, shows more accurate result. Keywords : fatwa, mustafti, mufti, fjtihad istimbathi, ijtihad tathbiqi, fatwa commission, 'ain al-ka'bah, and jihah al-ka'bah